University Students' Online Learning During COVID-19: The Role of Grit in Academic Performance - Sulla, Francesco; Aquino, Antonio; Rollo, Dolores (Frontiers in Psychology, 2022)
The governmental restriction due to COVID-19 pandemic led to Italian Universities moving teaching from face-to-face, to online. This represented an unexpected transition from traditional learning to what can be considered ‘e-learning’. This, together with the psychological distress that may be associated with the experience of lockdown, might have affected students’ performance. It was hypothesised that grit may be a protective factor in such situations. Indeed, compared to their less ‘gritty’ peers, individuals with higher levels of grit are expected to exhibit greater persistence in the pursuit of goals despite setbacks. Within educational contexts, grit is portrayed as a potentially important influence on outcomes such as achievement level, retention and probability of graduation. A longitudinal study was conducted using an online survey in order to assess the moderated mediation effect of grit on students’ achievement. One hundred seventy-six undergraduate students from two universities in the north of Italy participated in the survey. The results showed that grit affects students’ grades in final exams; perceived self-efficacy in the management of complex problems had a mediation effect on grades, while psychological distress moderated the first part of the mediation process. These novel findings extended our knowledge regarding the role of grit in academic performance investigating for the first time the role of self-efficacy and psychological distress in a learning carried out entirely online.